LEGAL REVIEW OF THE FINGERPRINT OBLIGATION IN NOTARY PRACTICE - Athaayaa Fausta Dyrianjaso; Arief Budiono (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the legal basis and responsibilities of notaries regarding the use of fingerprints as proof of identity in notarial practice. Furthermore, this study also seeks to assess the accuracy of fingerprints as authentic evidence that can guarantee the authenticity of legal documents and legal protection for the parties. The research method used is normative (doctrinal) legal research with a statutory approach and library research. Data were obtained through literature studies, analysis of laws and regulations, and interviews with notaries to strengthen the empirical findings. The research results show that fingerprints have a high accuracy rate (97–99%) in the identity verification process, making them legitimate for use as scientific evidence in notarial practice. Legally, the legal basis is derived from Law Number 2 of 2014 concerning the Position of Notary Public, the Civil Code, and Law Number 27 of 2022 concerning the Protection of Personal Data. Notaries are responsible for the use and storage of fingerprint data from the applicant. The application of the principle of prudence and personal data protection is essential to ensure that the identity authentication process does not result in legal violations. The conclusion of this study is that the mandatory use of fingerprints in notarial practice strengthens the authenticity of deeds, provides legal protection for the parties, and is an important step towards the digitalization of notaries that is safe and accountable